THE IMPLEMENTATION OF AUTOMATED ASSESSMENT PLATFORM IN ASYNCHRONOUS LEARNING FOR INDEPENDENT LEARNING OF GAME PROGRAMMING USER INTERFACE FOR STUDENTS AT TELKOM MALANG VOCATIONAL HIGH SCHOOL - Nurhasan, Usman; Nur Rahmanto, Anugrah; Usbah Mubarok, Faiz; Rahma Sabita, Almira (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The rapid development of the gaming industry has prompted the integration of programming education into vocational education curricula, yet manual assessment of student projects remains a significant constraint. This study proposes a C#-based game programming interface with automatic assessment using unit testing. Students receive learning materials from teachers for self-directed study, employing interface development methods based on Test-Driven Development (TDD) principles and prototype research methods. Research results demonstrate the success of automated assessment, enhancing the efficiency of student evaluations and the quality of game programming education. Academic data confirms improved student learning outcomes. Advantages of automated assessment include time efficiency for teachers, consistency, prompt feedback, support for self-directed learning, TDD implementation, and overall enhancement of learning quality. Data analysis of programming modules (MP) and test modules (MT) indicates the effectiveness of the C#-based game programming interface with TDD. Automated assessment eliminates the burden of manual correction, allowing teachers to focus on pedagogical aspects. Consistency is evident in uniform outcomes across all modules. Prompt feedback provides students with instant improvement opportunities, while self-directed learning support and TDD implementation are reflected in the success of test modules. In conclusion, this innovation effectively addresses assessment challenges in game programming education within vocational settings.